A situated approach to digital exclusion based on life courses - Laura Faure; Patricia Vendramin; Dana Schurmans (Internet Policy Review, 2020)
This article proposes a situational reading of digital exclusion. This is developed using an analytical approach based on life courses. The perspective is to analyse digital exclusion risks around the transitions and ruptures that shape the life courses. The research examines multiple stages within educational, professional and private trajectories and explores the uses of technology in these situations. It analyses the diversity of use in relation to the situations in which they take place and according to their significance at different points in life. Recognising the heterogeneity of courses and of individual experience, this approach allows us to work out the characteristics of digital uses and the potential risks of exclusion to which the individual is exposed.
Keywords: 300; Digital uses; Digital exclusion; Life course perspective; Digital autonomy; Situated approach